The Effects of Personal Pharmacogenetic Testing on the Effects of Pharmacy Student Perceptions of Knowledge and Attitudes Towards Precision Medicine - Dalga D Surofchy, PharmD (c); Sam Oh, PhD, MPH; Joshua Galanter, MD, MAS; Pin Xiang, PharmD; Megan Li, PhD (c); Su Guo, PhD; Tejal Desai, PhD; B Joseph Guglielmo, PharmD; Kathy Giacomini, PhD; Janel Long-Boyle, PharmD, PhD; Alan HB Wu, PhD; Esteban Burchard, MD, MPH (INNOVATIONS in Pharmacy, 2017)
Objective: To evaluate if pharmacy students’ participation in personal pharmacogenetic (Pgx) testing enhances their knowledge and attitude towards precision medicine (PM).